PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU BERDASARKAN STATUS SERTIFIKASI PADA SMK DI KECAMATAN SUKARAMI KOTA PALEMBANG - Eva Susanti (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
This study aimed to determine the influence level of motivation and work satisfaction on teacher’s performance based on the certification status at Vocational High Schools in Sukarami district Palembang. There were two problems in this study (1) Is there any influence of motivation and work satisfaction simultaneously on teacher’s performance based on certification status at Vocational High Schools in Sukarami district Palembang, and (2) Is there any influence of motivation and satisfaction on the teacher’s performance partially on teacher’s performance based on certification status at Vocational High Schools in Sukarami district Palembang. According to the test results based on multiple linear regression showed that (1) There was a positive influence and significant correlation between the variables of motivation and work satisfaction on teacher’s performance based on certification status, (2) There was a positive and significant influence between the variables of motivation on teacher’s performance based on certification status, (3) There was no positive and significant influence between the variables of work satisfaction on teacher’s performance based on certification status, (4) Certification status gave a positive and significant impact on teacher’s performance.